2010
DOI: 10.1007/s10701-009-9347-0
|View full text |Cite
|
Sign up to set email alerts
|

Einstein, Incompleteness, and the Epistemic View of Quantum States

Abstract: Does the quantum state represent reality or our knowledge of reality? In making this distinction precise, we are led to a novel classification of hidden variable models of quantum theory. We show that representatives of each class can be found among existing constructions for two-dimensional Hilbert spaces. Our approach also provides a fruitful new perspective on arguments for the nonlocality and incompleteness of quantum theory. Specifically, we show that for models wherein the quantum state has the status of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
624
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(643 citation statements)
references
References 56 publications
4
624
0
Order By: Relevance
“…[10], Definition 1. An ontological model is ψ-epistemic if there exists at least one pair of distinct quantum states, |ψ and |φ , such that the corresponding epistemic states µ ψ and µ φ have nonzero overlap, i.e., ω C (µ ψ , µ φ ) > 0.…”
mentioning
confidence: 99%
“…[10], Definition 1. An ontological model is ψ-epistemic if there exists at least one pair of distinct quantum states, |ψ and |φ , such that the corresponding epistemic states µ ψ and µ φ have nonzero overlap, i.e., ω C (µ ψ , µ φ ) > 0.…”
mentioning
confidence: 99%
“…It was then shown that mixed preparations (density matrices) in quantum theory exhibit preparation contextuality [9,12]. Interestingly, invoking another non-classical concept called steering [10,11] along with this new idea of preparation contextuality one can establish nonlocality of QM without using any Bell type inequalities; it has been shown that nonlocality of some hidden variable models, underlying QM, directly follows from the steerability of bipartite pure entangled states and the preparation contextuality of mixed states [12][13][14].The traditional definition of contexuality address to only the contexts of projective measurements, which has been studied in much depth [15,16]. However, generalized notion of contextuality developed by Spekkens define three different types of contexts: measurement (generalized), preparation, and transformation contexts [9].…”
mentioning
confidence: 99%
“…A precise formulation of these two alternatives, opening the way to clear-cut answers, was provided in [HS10]: if the wave-function corresponds to a real, ontic, property of physical systems, the preparation of a system in different pure quantum states should always result in different physical states. If, on the other hand, the wave-function has an epistemic status, such preparations should sometimes result in the same underlying physical state.…”
Section: Discussionmentioning
confidence: 99%
“…Following the formulation of Nicholas HARRIGAN and Robert W. SPEKKENS [HS10], the starting point is the assumption that every quantum system possesses a real physical state, generally called the ontic state, denoted λ. Somewhat similarly than in the Bell theorem (see sec-tion 1.2), we suppose that our present description of Nature could be incomplete, and that the real state λ of a physical system is not known to the present physics.…”
Section: ψ-Ontic and ψ-Epistemic Modelsmentioning
confidence: 99%